Legal qualification of internationalized internal armed conflicts (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Internationalized armed conflicts mean those conflicts that are originally internal armed conflicts between internal parties but at some point and in certain circumstances become international through an external armed intervention.The problem of the internationalized internal armed conflict lies in the fact that it contains a foreign element along with an internal element, which generates for us a mixed conflict that is neither international nor non-international, in addition to that it has no place in the texts of international humanitarian law, as this last law recognizes only two types of conflicts Armed (international and non-international).International humanitarian law applies different rules to armed conflicts of an international and non-international character, but from a humanitarian perspective, the difficulty of the situation lies in the fact that although there are special features that distinguish international internal armed conflicts from international and non-international armed conflicts, there are no compromises between The law applicable in situations of internal armed conflict and the law applicable to international conflicts.For international humanitarian law to apply to internationalized armed conflict, a process of legal qualification of the latter is necessary.This research aimed to define the concept of internationalized internal armed conflicts, and to indicate its most important characteristics, in addition to determining the legal qualification of this type of conflict.The research reached many results, most notably:• It cannot be said that the internationalized internal armed conflict is an international or a non-international conflict, as it contains a foreign element in addition to the internal element, which makes it a mixed conflict.• The mixed nature of internationalized armed conflicts proves the shortcomings and the difficulty of their qualification from a legal point of view, which leads to the difficulty of applying the provisions of international humanitarian law in their light, given the link between activating the rules of humanitarian protection with the dual classification of armed conflicts (international and non-international), the principle in the application of legal rules and the extent of qualification of the incident responding to legal standards.